Paheman Radyapustaka sebagai Skriptorium - Ahmad Alfan Rizka Alhamami (Manuskripta, 2020)
Since its establishment on October 28, 1890, Paheman Radyapustaka has only been known for its function as a museum. The main activity of Paheman Radyapustaka is as a place for writing, copying, and collecting Surakarta manuscripts, so that Paheman Radyapustaka deserves to be called a Scriptorium. This paper aims to reveal the production activities of the Paheman Radyapustaka scriptorium which includes the writers / copyists, the writing results, and the genre. The method in this paper is a method of codicological studies that includes history, writers / copyists, and scriptorium collections. The results of the search through the archives and manuscript colophon of the Paheman Radyapustaka scriptorium were that of the 400 manuscripts in his collection, there were 82 manuscripts written by the Scripts of the Scriptures. The scribes of the Paheman Radyapustaka Scriptorium were Wirapustaka, Sastrasayana, Dayapangreka, Karyarujita and the residents. The genres written by the scribes of the Paheman Radyapustaka scriptorium are macapat and gancaran.